Influence of Accessibility and Amenity on Visitor Satisfaction at Sikulikap Waterfall, Karo Regency, North Sumatra - Yohannes Ebenezer Situmorang (Jurnal Manajemen Bisnis Eka Prasetya, 2024)
Sikulikap Waterfall Nature Tourism is one of the most popular tourist destinations in Karo Regency. On weekends and national holidays Sikulikap Waterfall is always full of visitors. However, it turns out that there are still problems regarding visitor satisfaction at Sikulikap Waterfall. The purpose of this research is to identify accessibility, amenities, visitor satisfaction and analyze how accessibility and amenities influence visitor satisfaction. The research method used in this study is a quantitative associative approach while the research. There are two types of data used, namely primary data and secondary data. The tools in this research are questionnaires, observation, and documentation. The number of samples in the study were 100 respondents to Sikulikap Waterfall. Partially the accessibility variable has a positive and significant effect on visitor satisfaction with the result t-test 2.151 > t-table 1.984. Amenity variables partially have a positive and significant effect on visitor satisfaction with t-count results of 5,347 > 1.984, then simultaneously accessibility and amenity variables have a positive and significant effect on visitor satisfaction with F-count results of 72,735 > 3.09 and coefficients of determination of accessibility and amenity explains visitor satisfaction with an Adjusted R Square value of 59.2%, so the hypothesis is accepted